9th anniversary of JCHIMP. Issue 2 (3rd March 2020) - Ferguson, Robert; Alweis, Richard
ABSTRACT: We have completed volume 9 of the Journal of Community Hospital Internal Medicine Perspectives â€" JCHIMP. In this perspective piece we discuss the many achievements of our journal, including our impact factor, the diversity of institutions publishing, our editorial board, and the importance of our reviewers.